Biogenesis of Exosomes Laden with Metallic Silver–Copper Nanoparticles Liaised by Wheat Germ Agglutinin for Targeted Delivery of Therapeutics to Breast Cancer. Issue 7 (10th April 2022) - Ashraf, Sarmadia; Qadri, Shahnaz; Akbar, Shayista; Parray, Aijaz; Haik, Yousef
Abstract: The anticancer property of silver–copper metallic nanoparticles (AgCu‐NPs) is of greater interest in cancer therapeutics; however, its off‐target toxicity limits its therapeutic application. Exosomes emerge as one of the leading idiosyncratic nanocarrier choices for cancer therapeutics due to their size, stability, and phenotypic diversity; however, to encapsulate NPs in extracellular vesicles (EVs) without disrupting their inherited functions is far from the expectations. Here, the loading strategy of AgCu‐NP conjugated with wheat germ agglutinin (AgCu‐NP‐WGA) in exosomes during biogenesis for the targeted delivery of anticancer therapeutics to breast cancer is reported. Based on the intrinsic mechanism of endocytosis of WGA, results show that internalization of WGA or AgCu‐NP‐WGA bypasses the lysosomal pathway and recycles in EVs. On the contrary, the transport of naked AgCu‐NPs to lysosomes; mechanistically, an acidic environment causes oxidation of AgCu‐NP. Next, the analysis of EVs harvested by differential centrifugation shows that only AgCu‐NPs‐WGA (Exo‐NP) retain their metallic state. Furthermore, Exo‐NP cytotoxicity results manifest that MCF10A‐derived Exo‐NPs are toxic to its homologous breast cancer cells (MCF‐7 and MDA‐MB 231) and nontoxic to heterologous cancers NC1‐1975 and MCF 10A. In conclusion, this study shows the self‐assembly of AgCu‐NP in exosomes to target and deliver therapeutics for breast cancer. Abstract : A method of self‐loading anticancer‐AgCu nanoparticles (NPs) in exosomes during their biogenesis guided by wheat germ agglutinin bypasses the lysosomal pathway. As a result, exosomes laden with NPs are released from healthy cells, showing preferential toxicity to its homologous breast cancer cells. Hence, this study shows the targeted delivery of anticancer therapeutics to breast cancer.